The Implementation of Gratitude-Based Strategies to Mitigate Envy in Senior High School Students - Sukma Ayu Fadhila Ardianing; Muhammad Elsa Nuril Azzar; Sufirmansyah Sufirmansyah (Universitas Nurul Jadid, 2026)
This article aims to analyze the process of internalizing gratitude and its role in minimizing envy among tenth-grade students at Miftahul Huda Ngreco Islamic Senior High School. The study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving five students and one Akidah Akhlak teacher. Data were analyzed through data reduction, data display, and conclusion drawing, supported by triangulation and member checking to ensure validity. The findings show that envy among students appears in three forms, namely envy toward physical appearance and material possessions, academic achievement and intellectual ability, and spiritual quality. The emergence of envy is influenced by social comparison, low self-acceptance, social media exposure, and peer environment. The madrasah internalizes gratitude through instructional integration, reflective learning, habituation, and teacher modeling. The internalization process occurs across cognitive, affective, and behavioral dimensions, leading to changes in students’ mindset, emotional stability, and actions. The results indicate that gratitude effectively reduces envy by decreasing social comparison, increasing self-acceptance, and fostering positive social relationships. This article implies that gratitude can function as both a religious value and a psychological strategy in character education to minimize negative emotions among students.